Anticancer properties of lipid and poly(ε-caprolactone) nanocapsules loaded with ferrocenyl-tamoxifen derivatives. (23rd August 2018) - Najlaoui, Feten; Pigeon, Pascal; Aroui, Sonia; Pezet, Mylène; Sancey, Lucie; Marrakchi, Naziha; Rhouma, Ali; Jaouen, Gérard; De Waard, Michel; Busser, Benoit; Gibaud, Stéphane
Abstract: Objective: We synthesized new tamoxifen derivatives as anticancer drug candidates and elaborated on convection-enhanced delivery (CED) as a strategy for delivery. Methods: To overcome the issue of their poor solubility, these ferrocenyl-tamoxifen derivatives were esterified and encapsulated into different nanocarriers, that is lipid (LNC) and polymeric nanocapsules (PNL-NC). We describe the chemistry, the encapsulation and the physicochemical characterization of these formulations. Key findings: Starting compounds [phthalimido-ferrocidiphenol and succinimido-ferrocidiphenol], esterified prodrugs and their nanocapsules formulations were characterized. These drug candidates displayed a strong in vitro activity against breast and glioblastoma cancer cells. The ester prodrugs were toxic for glioblastoma cells (IC50 = 9.2 × 10 −2 μm and 6.7 × 10 −2 μm, respectively). The IC50 values for breast cancer cells were higher for these compounds. The encapsulation of the esterified compounds in LNCs (≈50 nm) or PCL-NCs (≈300 nm) did not prevent their efficacy on glioblastoma cells. These anticancer effects were due to both blockade in the S-phase of the cell cycle and apoptosis. Moreover, the tamoxifen derivatives-loaded nanocapsules induced no toxicity for healthy astrocytes and showed no haemolytic properties. Loaded Lipid Nanocapsules (LNCs) presented interesting profiles for the optimal delivery of active compounds. Conclusions: Phthalimido- and Succinimido-esters represent an innovative approach to treat cancers with cerebral localizations such as glioblastoma or brain metastases from breast cancers.